A new survey for high velocity HI detections in the southern hemisphere - Morras, Ricardo (2000)
A new high-sensitivity HI survey of the southern sky was made south of Declination , at the Instituto Argentino de Radioastronomía (IAR), on a half-degree grid in galactic coordinates. A total of 50980 positions were observed. One of the goals of this survey was to search for high velocity clouds (HVCs). The HI profiles have been smoothed to a velocity resolution of 8 km s-1. The resulting rms noise falls in the range 0.015 to 0.020 K. We have detected 6848 high velocity (HV) components.